Detailed Seed Cone Morpho-Anatomy Provides New Insights into Seed Cone Origin and Evolution of Podocarpaceae; Podocarpoid and Dacrydioid Clades - Raees Khan; Robert S. Hill; Veit M. Dörken; Ed Biffin (Plants, 2023)
The study of reproductive morphology and trait evolution provides a vital insight to understand the evolutionary history of plants. The conifer family Podocarpaceae has a remarkable diversity of seed cones, with distinct morphology among the genera and with conifers in general. However, we lack a good understanding of the seed cone morpho-anatomy and trait evolution of Podocarpaceae. We investigated detailed seed cone morpho-anatomy using staining and sectioning techniques to clarify the anatomical, morphological diversity and evolution of functional traits. The presence of a fleshy receptaculum is a characteristic feature of both clades. However, species of Retrophyllum, Afrocarpus and some species of Nageia and Podocarpus form a fleshy sarcotesta-like seed coat, lacking a fleshy receptaculum. The ancestral state reconstructions show a shift between and sometimes within the genus. Although both clades demonstrate fleshiness as an ancestral trait, the shift in fleshy structures provides evidence for complex multiple evolutions of fleshy morphologies. These seed cone traits (e.g., fleshiness and size), along with the broad, flattened and well-adapted (leaf dimorphism) foliage in both clades, are largely congruent with efficient light harvesting and bird dispersal. These traits make these two clades well adapted to their environment, when growing in communities including tall and broad-leaved angiosperms (closed-canopy angiosperm forests), compared to other podocarps, making them more successful in achieving a wider distribution and species richness.